2020
DOI: 10.1002/jclp.23092
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of smartphone compassion training on stress among Swedish university students: A pilot randomized trial

Abstract: Objective To investigate the effects of a 6‐week smartphone compassion training intervention on mental health. Method Fifty‐seven Swedish university students (mean age = 25, SD = 5) reporting high levels of stress were randomized to compassion training (n = 23), mindfulness (n = 19), or waitlist (n = 15). Result Multilevel models indicated that both compassion and mindfulness training increased self‐compassion compared to the waitlist, while only compassion significantly reduced stress. Between‐group effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 98 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…Acknowledging and exploring the role the inner critic plays, and trying to meet the critic's needs by responding with a compassionate mind is an important cornerstone in CFT [2,5,24]. Using an app based on the CFT model appeared to initiate greater self-awareness, self-kindness, and self-compassion, and helped participants work toward befriending their self-critic, which supports the findings of Andersson et al [25], who found that compassion training via a smartphone application improved levels of self-compassion.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Acknowledging and exploring the role the inner critic plays, and trying to meet the critic's needs by responding with a compassionate mind is an important cornerstone in CFT [2,5,24]. Using an app based on the CFT model appeared to initiate greater self-awareness, self-kindness, and self-compassion, and helped participants work toward befriending their self-critic, which supports the findings of Andersson et al [25], who found that compassion training via a smartphone application improved levels of self-compassion.…”
Section: Discussionsupporting
confidence: 53%
“…This study is the first to examine how a 28-day course, introducing new aspects of the CFT model each day, might be helpful. Another study that quantitatively evaluated the effectiveness of a CFT smartphone app found the app improved levels of self-compassion [25]. This paper reports on the qualitative aspect of the study.…”
Section: The Projectmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, new forms of online interventions based on self-compassion meditation and self-compassion writing therapy for patients with mental illness have been developed and have demonstrated positive effects. The intervention time is also getting shorter [6 weeks ( Finlay-Jones et al, 2017 ; Rodgers et al, 2018 ; Andersson et al, 2020 ), 4 weeks ( Mak et al, 2018 , 2019 ; Beshai et al, 2020 ), 3 weeks ( Albertson et al, 2015 ; Toole and Craighead, 2016 ), 2 weeks ( Kelman et al, 2018 ; Stevenson et al, 2019 ; Halamová et al, 2020 , 2021 ; Schnepper et al, 2020 ; Seekis et al, 2020 ), and 1 week ( Shapira and Mongrain, 2010 ) or less ( Galla, 2016 )]. For example, Albertson et al (2015) randomized participants to either an intervention group (meditation via podcast) or a waitlist control group.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the advent of apps and mobile technology, various online interventions have been created with the intention of cultivating mindfulness and compassion. Systematic reviews and meta-analyses have suggested that these interventions may be helpful in increasing mindfulness and self-compassion, whilst also reducing psychological distress [27][28][29]. Due to the social distancing restrictions in place because of the coronavirus outbreak, developing online interventions seems more relevant than ever.…”
Section: Introductionmentioning
confidence: 99%